2012
DOI: 10.1002/ange.201201787
|View full text |Cite
|
Sign up to set email alerts
|

Katalytische selektive Synthese

Abstract: Der Verlauf und das Produkt einer Reaktion lassen sich gezielt über die Katalysatorstruktur steuern, selbst bei nahezu identischen Reaktionsbedingungen. Katalysatorkontrollierte Selektivität ist in der enantioselektiven Synthese gut etabliert, in katalytischen regio‐, chemo‐ und produktselektiven Reaktionen aber wenig verbreitet. Dieser Aufsatz beschreibt, wie eine Ausgangsverbindung lediglich durch die Auswahl des Katalysators selektiv in zwei oder mehr unterschiedliche Produkte umgewandelt werden kann. Wir s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(38 citation statements)
references
References 309 publications
(223 reference statements)
0
35
0
3
Order By: Relevance
“…[9,10] However, using catalyst control to overturn the inherent siteselectivity of as ubstrate is still ac hallenging task. [9,10] However, using catalyst control to overturn the inherent siteselectivity of as ubstrate is still ac hallenging task.…”
Section: Angewandte Zuschriftenmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10] However, using catalyst control to overturn the inherent siteselectivity of as ubstrate is still ac hallenging task. [9,10] However, using catalyst control to overturn the inherent siteselectivity of as ubstrate is still ac hallenging task.…”
Section: Angewandte Zuschriftenmentioning
confidence: 99%
“…This study led us to establish ah ighly enantioselective Diels-Alder reaction between av ariety of 3-alkyl quinone imine ketals and diene carbamates catalyzed by axially chiral dicarboxylic acids (R)-1 ( Figure 1c). [9,10] This counter-intuitive selectivity will be explained by considering the E/Z isomerization of the imino functionality which acts as af luxional directing group. This site-divergent strategy enabled the synthesis of cycloadducts having an all-carbon quaternary stereocenter while leaving the lesshindered C = Cb ond for later transformation.…”
mentioning
confidence: 99%
“…[4b,c] Recently,i tw as found that fused aromatic systems bearing internal nitrogen, such as azacorannulene [5] and azafullerenes, [6] have shown interesting electronic and optical properties in energy conversion applications.F or the synthesis of fused N-heterocycles,d ivergent reactions would be ideal if controlled stereospecifically,chemospecifically,and regiospecifically from common starting materials. [7] Further, cyclo-isomerization is aversatile strategy for creating cyclic organic compounds from acyclic starting materials in an atomeconomical manner. [8] If possible,asimultaneous multiple ring fusion will be highly desirable for more complex molecules.…”
mentioning
confidence: 99%
“…[15] However,i ntramolecular baddition of aryl groups to ynamine is unprecedented to the best of our knowledge [10a] and these cycloisomerizations occurred regardless of the electronic nature of the C2phenyl ring due to the high reactivity of ynamine.I nterestingly,w hen PdCl 2 was used with external oxidant, [16] ac yclodimerized product 4 was obtained. Alternatively,t he synthesis of as imple benzo [7,8]indolizino[2,3,4,5-ija]quinoline 8 was demonstrated through alkyne addition and sequential double cyclization.…”
mentioning
confidence: 99%
“…[1] Even though the development of catalytic approaches has allowed tremendous progress in the ability to form products in as elective fashion, the ability to access the full array of isomers in ad ivergent fashion remains ac hallenge.F or transition-metal-catalyzed allylic alkylation of nucleophiles,areaction which represents one of the fundamental carbon-carbon and carbon-heteroatom bond-forming reactions (Figure 1a), the most important selectivity issues are the control of regio-and stereoselectivity.I nt he last decades,r emarkable progress has been made in the area of stereoselective allylations of nucleophiles and alarge number of asymmetric versions have been disclosed. In the last decades,catalysis has been established as the stateof-the-art method for performing reactions in an efficient and selective manner.…”
mentioning
confidence: 99%